Effects of Hydrolysable Tannin Supplementation on Nutrient Intake, Milk Production and Milk Somatic Cell Count in On-farm Dairy Cows - Prapaiwong, Tipwadee; Wachirapakorn, Chalong; Jarassaeng, Chaiwat; Srakaew, Wuttikorn; Poolthajit, Sukanya (Trends in Sciences, 2022)
This study examined the effects of hydrolysable tannin (HT) supplementation on nutrient intake, milk production and milk somatic cell count in on-farm dairy cows. Fifty-four Holstein Friesian crossbred cows weighing 450 to 500 kg and were subjected to an experiment for 49 days. Dairy cows were divided into 3 groups, which were 1) the control group without HT supplementation and the HT supplementation groups, which received HT products (15 g/day), 2) one contains 3.15 g/day of HT and 3) another contains 6.30 g/day of HT. Hydrolysable tannin was extracted from sweet chestnut wood (Castanea Sativa Mill.). Dairy cows received HT products on the top of concentrate (22 % CP) in the morning after milking. Total mixed ration (TMR), pangola grass (Digitaria eriantha) hay and concentrate were offered according to animal nutrient requirements. The results showed that supplementation of HT has no influence (p > 0.05) on the nutrient intake, milk yield and milk composition when compared to the control group. In addition, the increased levels of HT caused quadratic increases in fat:protein at pre-treatment and treatment periods (p < 0.05; p = 0.06, respectively), while differential somatic cell count (DSCC) at treatment and post-treatment periods showed a quadratic decrease (p < 0.05; p < 0.05, respectively), with supplementation of HT product containing 6.30 g HT/day (p < 0.05) being the lowest. Therefore, it can be concluded that supplementation with HT product does not affect nutrient intake, milk yield, however, it could reduce DSCC and probably improve udder health in on-farm dairy cows. HIGHLIGHTS A quantitative performance comparison of Radio over Free Space Optical links WDM increases the capacity while the MIMO links help to maintain the transmission range A combination of WDM and MIMO RoFSO links is identified to be the best